Temperature-responsive emission and elastic properties of a new 2D lead halide perovskite - Fan, Jia-Hui; Qin, Yan; Azeem, Muhammad; Zhang, Zhuo-Zhen; Li, Zhi-Gang; Sun, Na; Yao, Zhao-Quan; Li, Wei (Dalton transactions : an international journal of inorganic chemistry, 2021)
Two-dimensional (2D) organometallic halide perovskites (OHPs) are promising optoelectronic materials because of their excellent stability and tunable band gaps. Herein, we report the optical and elastic properties of a newly synthesized 2D lead halide perovskite, (C 9 H 14 ON) 2 PbI 4 (C 9 H 14 ON + = 4-methoxyphenethylammonium), by a combined experimental and theoretical approach. Our experiments demonstrate that (C 9 H 14 ON) 2 PbI 4 shows a strong green emission under ambient conditions which is ascribed to its band gap of 2.4 eV. Moreover, our temperature-dependent photoluminescence (PL) experiments in the temperature range of 143-283 K reveal that the green emission red-shifts with increasing temperature, which is primarily attributed to the synergistic effect of thermal expansion and electron-phonon interactions. The elastic properties, obtained from density functional theory calculations, reveal that (C 9 H 14 ON) 2 PbI 4 has relatively low modulus and anisotropy compared with other 2D materials. Here, the optical and elastic properties of a newly synthesized 2D lead halide perovskite were systematically investigated via a combined theoretical-experimental approach.